Targeted inhibition of the WEE1 kinase as a novel therapeutic strategy in neuroendocrine neoplasms - Weindl, Lena; Atreya, Imke; Dietrich, Peter; Neubeck, Sabine; Neurath, Markus; Pavel, Marianne Ellen (Endocrine-Related Cancer, 2021)
Neuroendocrine neoplasms (NENs) represent a rare and heterogeneous group of malignancies, sharing features of both neural and endocrine cells. NENs G3 appear as a highly aggressive subset with a poor prognosis and limited therapeutic options. The small-molecule inhibitor of the WEE1 tyrosine kinase, adavosertib (AZD1775), has previously demonstrated potent anti-tumor effects on various types of cancer in preclinical and clinical studies. However, the role of adavosertib in NENs G3 had remained elusive. We evaluated the effects of adavosertib on pancreatic (BON-1, QGP-1) and bronchopulmonary (NCI-H720) neuroendocrine tumor cell lines applying 2D and 3D spheroid models. We newly demonstrated that adavosertib is sufficient to reduce cell viability and proliferation in neuroendocrine cell lines with features of high-grade NENs. As underlying mechanisms, we identified adavosertib-mediated DNA double-strand breaks and a G2/M cell cycle checkpoint abrogation leading into mitotic catastrophe and cancer cell apoptosis. Silencing of WEE1 via siRNA transfection resulted in a phenotype similar to adavosertib treatment. Together, inhibition of the WEE1 tyrosine kinase applying adavosertib on NENs G3 outlines a promising novel therapeutic strategy.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 3D cell culture; Cell cycle; G3; Neuroendocrine neoplasm; WEE1